2023
DOI: 10.1039/d3tc00806a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible/wearable resistive gas sensors based on 2D materials

Abstract: Flexible/wearable gas sensor technology is gaining huge interest in the current era of the Internet of Things for its applications in personal environmental monitoring, healthcare, and safety. In this respect,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 143 publications
0
12
0
Order By: Relevance
“…The main disadvantages of pure TMDs-based chemiresistive-type gas sensors are often their low sensitivity and erratic response signals with noticeable drift. 240 To solve this issue, pure TMDs were mixed with secondary phases such as metal oxides and noble metals. 241 Guang, Q. et al , reported that the sensors made of Fe 3 O 4 /WS 2 heterostructures showed a notable enhancement in their ability to detect ammonia at ambient temperature, in comparison to the sensors made from bare WS 2 .…”
Section: Experimental Investigations Of Wse2-based Gas Sensorsmentioning
confidence: 99%
“…The main disadvantages of pure TMDs-based chemiresistive-type gas sensors are often their low sensitivity and erratic response signals with noticeable drift. 240 To solve this issue, pure TMDs were mixed with secondary phases such as metal oxides and noble metals. 241 Guang, Q. et al , reported that the sensors made of Fe 3 O 4 /WS 2 heterostructures showed a notable enhancement in their ability to detect ammonia at ambient temperature, in comparison to the sensors made from bare WS 2 .…”
Section: Experimental Investigations Of Wse2-based Gas Sensorsmentioning
confidence: 99%
“…First, NO 2 is a harmful gas found in the atmosphere that can cause damage to various parts of the human body, such as the eyes, nose, throat, and respiratory system [122][123][124]. To protect workers from the danger of this gas, a detection system is used that operates through chemical gas sensing [125][126][127][128][129][130]. This allows for an early warning system to prevent respiratory damage caused by toxic air pollutants.…”
Section: Wearable Sensors For Danger Detectionmentioning
confidence: 99%
“…The ever-increasing industry units and living standards have led to a rise in environmental hazards, resulting in pollution and toxic gases affecting our daily lives in various direct and indirect ways [1]. Gas sensor devices have proven to be effective in detecting toxic gases in the open atmosphere and gas leakages in industries, making them essential in smart houses and industries such as automotive plants, chemical plants, nuclear plants, and oil and gas applications [2,3]. Both SO 2 and COCl 2 are hazardous gases.…”
Section: Introductionmentioning
confidence: 99%
“…3 , COCl 2 , NH 3 , NO 2 , and SO 2 are tested on different sites of monolayers. The adsorption behavior is tested in terms of the adsorption energy, recovery time, adsorption height, Bader charge, CDD, and electronic properties.…”
mentioning
confidence: 99%